2007
DOI: 10.1104/pp.107.097584
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of T-Phylloplanin Gene Knockdown and of Helianthus and Datura Phylloplanins on Peronospora tabacina Spore Germination and Disease Potential

Abstract: T-phylloplanin proteins secreted to aerial surfaces of tobacco (Nicotiana tabacum) by short procumbent trichomes inhibit spore germination and blue mold disease caused by the oomycete pathogen Peronospora tabacina. Many other plants were found to contain water-washed leaf surface proteins (phylloplanins), but the functions and properties of these are not known. Here we extend earlier evidence for the antifungal activity of T-phylloplanins using a reverse genetics approach. RNA interference of the T-phylloplani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 19 publications
5
31
0
Order By: Relevance
“…These chemicals have previously shown antifungal, insecticidal, and antibacterial properties (14,19,20,22,29,37,38) but have not been studied for black shank prevention. There are preliminary indications that cis-abienol and phylloplanin have a potential against black shank in laboratory conditions (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These chemicals have previously shown antifungal, insecticidal, and antibacterial properties (14,19,20,22,29,37,38) but have not been studied for black shank prevention. There are preliminary indications that cis-abienol and phylloplanin have a potential against black shank in laboratory conditions (22).…”
Section: Discussionmentioning
confidence: 99%
“…A tobacco phylloplanin (T-phylloplanin) was isolated from TI 1068, and characterized as a protein produced and secreted by tobacco short glandular trichomes. T-phylloplanin was found to be active against blue mold spores (19)(20)(21), and also to delay black shank infection of the roots of dark tobacco in a tube and a soil drench assay (22). cis-Abienol is a valuable natural product synthesized by glandular trichomes and secreted in the leaf gum in some tobaccos (23,24).…”
Section: Resumementioning
confidence: 99%
“…In addition to secreting small molecules (for example acyl sugars), recent evidence indicates that trichomes of tobacco actively secrete water-soluble low-molecularweight glycoproteins, known as phylloplanins, to the leaf surface (Kroumova et al, 2007;Shepherd et al, 2005). These studies demonstrated that phylloplanins can inhibit spore germination and the onset of blue-mold disease caused by the oomycete pathogen Peronospora tabacina; tobacco plants with reduced levels of phylloplanin mRNA and protein are more susceptible to pathogen infection.…”
Section: Trichome Defense Proteinsmentioning
confidence: 99%
“…These small proteins deposited at the leaf surface thus represent an early line of defense against microbial invaders. Pathogen spore germination assays using water-soluble leaf proteins from other plants showed that leaf surface-localized antimicrobial proteins are not restricted to tobacco (Kroumova et al, 2007). However, it is not yet known whether the leaf surface proteins on other plants are homologous to the tobacco phylloplanins.…”
Section: Trichome Defense Proteinsmentioning
confidence: 99%
“…Development of anti‐tumor drugs are the duty of medical workers. In the new drug research procedure, finding an active leading compound is the foundation of all the research work …”
Section: Introductionmentioning
confidence: 99%